2009 International Conference on Electromagnetics in Advanced Applications 2009
DOI: 10.1109/iceaa.2009.5297299
|View full text |Cite
|
Sign up to set email alerts
|

Shaping and resizing of multifed slot radiators used in conformal microwave antenna arrays for hyperthermia treatment of large superficial diseases

Abstract: It has been recently shown that chestwall recurrence of breast cancer and many other superficial diseases can be successfully treated with the combination of radiation, chemotherapy and hyperthermia. Conformal microwave antenna array for hyperthermia treatment of large area superficial diseases can significantly increase patient comfort while at the same time facilitate treatment of larger and more irregularly shaped disease. A large number of small efficient antennas is preferable for improved control of heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The stacked phantom consisted of a 5 mm fat layer on top, a 28 mm muscle phantom in the middle and a 5 mm fatlayer at the bottom. Heating was done with a single Dual Concentric Conductor (DCC) antenna [13, 14] at 915 MHz through a bolus of circulating water. The input power to the top antenna was approximately 20 W at 915 MHz.…”
Section: Resultsmentioning
confidence: 99%
“…The stacked phantom consisted of a 5 mm fat layer on top, a 28 mm muscle phantom in the middle and a 5 mm fatlayer at the bottom. Heating was done with a single Dual Concentric Conductor (DCC) antenna [13, 14] at 915 MHz through a bolus of circulating water. The input power to the top antenna was approximately 20 W at 915 MHz.…”
Section: Resultsmentioning
confidence: 99%
“…The average depth of the kidney was measured as 3.5cm to the renal pelvis from the skin. EM computer simulations of the 915 MHz DCC antenna indicated that multiple warming antennas minimized skin and intervening tissue warming and maximized the warming of urine in the bladder [7, 8]. A DCC antenna array with two 3 × 3 cm square elements operating incoherently at 915 MHz was found to be the best for bladder warming through a thin layer (7–10mm) of deionized waterbolus at room temperature [9].…”
Section: Resultsmentioning
confidence: 99%
“…Due to smaller urine volume (75 mL) in the experimental setup, a modified version of the single square Dual Concentric Conductor [7, 8] microwave antenna (5 cm wide) was used for phantom studies to deposit microwave power inside the 4.22 cm wide urine phantom at depth. Thus, power was applied to a single element DCC test antenna that was directed into the multilayer waterbolus-fat-muscle load and into the urine filled bladder (75 ml).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, superficial antennas with various effective field sizes allowing adequate treatment of both small and larger tumor areas have been developed. This has resulted in clear progress in the quality of superficial heating equipment [310][311][312][313][314][315].…”
Section: Clinical Applications Of Intraluminal Hyperthermia and Hivecmentioning
confidence: 99%